Earthrise : the story of the photograph that changed the way we see our planet - Marcus, Leonard S., 1950- (Farrar Straus Giroux, 2025)
"From renowned researcher and children's lit scholar Leonard S. Marcus comes a middle-grade nonfiction book about the astonishing photograph taken during the Apollo 8 mission that forever shifted the way we view our planet"--